ESTRATEGIAS METODOLÓGICAS Y SU INCIDENCIA EN LA LECTOESCRITURA DE LOS ESTUDIANTES DEL 4TO AÑO EGB DE LA UNIDAD EDUCATIVA ADOLFO MARÍA ASTUDILLO, BABAHOYO, 2023. - ROSERO ZAMBRANO DENNYS JAMILET (2024)
Methodological strategies are defined as those actions and activities that teachers establish in their planning to coordinate, organize, apply and improve their way of teaching, promoting meaningful learning and improving reading and writing skills. For this reason, the main objective of the study is to determine the incidence of methodological strategies in the reading and writing of the 4th year EGB students of the Adolfo María Astudillo Educational Unit of the Babahoyo canton. The methodology used in the case study conforms to a qualitative approach; While the research was descriptive and field, the population is made up of 34 students and their teacher tutor from the 4th year EGB parallel B of the Adolfo María Astudillo Educational Unit and taking a sample of 15 students, who present problems in reading and writing and your tutor teacher. It is important to mention that to obtain relevant information on the topic, two techniques were used: direct observation, directed at the students, and an interview with the teacher. The results obtained in this study are that in the 4th year EGB “B” of the Adolfo María Astudillo Educational Unit, adequate strategies are not applied to promote reading-writing habits, therefore, students have problems reading fluently and writing without grammatical errors. However, not all of this responsibility falls on the teacher, since educational institutions do not have the necessary teaching resources to promote quality education that responds to the needs of each student.